03.05 The tam receptors axl and mer play a protective role in a temporal and spatial manner in inflammatory arthritis. (1st March 2017) - Waterborg, Claire E.J.; Través, Paqui G; Beermann, Silke; Koenders, Marije I; Lemke, Greg; van de Loo, Fons A.J.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterised by an inflammatory response in synovial joints. One family of tyrosine kinase receptors that mediates an anti-inflammatory feedback mechanism are Tyro3, Axl and Mer (gene Mertk ; TAM). The role of TAM receptors in RA has not been elucidated and we studied the role of Axl and Mer in an experimental model of RA. Materials and methods: The KRN serum transfer model of arthritis was induced by two intraperitoneal injections of arthritic K/BxN serum in Axl -/-, Mertk -/-, Axl -/- Mertk -/- and wild-type (WT) mice. Ankle joints were macroscopically scored for 7 days. At day 0, 2 and 7, ankle and knee joints were isolated for histology and immunohistochemistry. Results: Mertk -/- mice had increased macroscopic ankle scores until day 4 whereas Axl -/- mice had enhanced macroscopic scores from day 4 until day 7. Histology of ankle joints showed significantly more inflammation in Mertk -/- mice at day 2 and increased arthritis pathology in Axl -/- mice at day 7, reflecting macroscopic ankle scores. Histological analysis of ankle joints of Axl -/- Mertk -/- mice at day 7 showed enhanced pathology compared to both Axl -/- and WT mice, indicating an additive effect of Axl and Mer deficiency. In contrast to the ankle joints at day 7, enhanced macroscopic scores and arthritis pathology in knee joints of Mertk -/- mice, compared to WT mice, was observed. To explain the discrepancy of Axl involvement between ankle and knee at day 7, we examined Axl expression in synovium before the onset of arthritis. The cells in the lining layer of ankle synovium were strikingly Axl positive whereas the synovium of the knee joints was Axl negative. Conclusions: These findings identify the TAM receptors Axl and Mer as important players in arthritis. The Mer receptor plays a protective role at the onset of arthritis whereas the Axl receptor takes over this role in established disease in ankle joints. In the knee joints, however, Mer but not Axl, plays a prominent protective role, likely due to the lack of Axl in naïve knee joints. These findings highlight differences in topographically distinct synovial joints in inflammatory arthritis.